Oxidation of sulfide removal from petroleum refinery wastewater by using hydrogen peroxide - M. C., Mamat; Ahmad Bazli, Bustary; Abdul Aziz, Mohd Azoddein (IOP Publishing Ltd, 2020)
Petroleum refinery wastewater typically has high concentration of sulfide which is known as the most hazardous pollutants. It is released to the environment either as dissolved sulfide (S2- and HS-) in effluents or as H2S in waste gases. The objective in this study is to determine the effectiveness of hydrogen peroxide (H2O2) in sulfide removal. The best sulfide concentration, dosage and reaction time were determined. The removal of sulfide from petroleum refinery wastewater via oxidation method by using hydrogen peroxide (H2O2) is presented in this study. The treated wastewater was analyzed by spectrophotometer. Result shows that the best concentration of sulfide simulated wastewater (300 mg/L), H2O2 dosage (1.5 ml) and reaction time (30 min) able to reduce 97.67%, 98.22% and 98.89% of sulfide concentration from simulated wastewater. Thus, sulfide removal from the actual petroleum refinery wastewater which is spent caustic by using H2O2 was able to reduce 99.83% (0.5 mg/L) sulfide concentration. Besides that, Chemical Oxygen Demand (COD) concentration was reduced to 98.29% (70 mg/L) and pH 8.41 after treatment. Thus, it is concluded that oxidation method by using H2O2 is effective in sulfide removal as well as COD, and pH from spent caustic. It does meet requirement from Department of Environment (DOE) for sulfide, COD and pH which are 0.5 mg/L, 100 mg/L and 5.5 – 9.0, respectively. The information obtained from this study is useful for scale up purpose in the petroleum refining industry that choose H2O2 via oxidation method to remove sulfide from spent caustic wastewater.